Vitamin D receptor and epigenetics in HIV infection and drug abuse - Chandel, Nirupama; Malhotra, Ashwani; Singhal, Pravin C. (Frontiers in Microbiology, 2015)
Illicit drug abuse is highly prevalent and serves as a powerful co-factor for HIV exacerbation. Epigenetic alterations in drug abuse and HIV infection determine expression of several critical genes such as vitamin D receptor (VDR), which participates in proliferation, differentiation, cell death under both physiological and pathological conditions. On that account, active vitamin D, the ligand of VDR, is used as an adjuvant therapy to control infection, slow down progression of chronic kidney diseases, and cancer chemotherapy. Interestingly, vitamin D may not be able to augment VDR expression optimally in several instances where epigenetic contributes to down regulation of VDR; however, reversal of epigenetic corruption either by demethylating agents (DACs) or histone deacetylase (HDAC) inhibitors would be able to maximize expression of VDR in these instances.